Variation in Root Traits and Root-Endophyte Interactions in Primary Synthetic Wheat Derived from Aegilops tauschii Collected from Diverse Soil Types - Ahmed Khaled Hassan Mohammedali; Nasrein Mohamed Kamal; Yasir Serag Alnor Gorafi; Izzat Sidahmed Ali Tahir; Hisashi Tsujimoto; Takeshi Taniguchi (Agronomy, 2025)
Modern wheat breeding has largely emphasized aboveground traits, often at the expense of belowground characteristics such as root biomass, architecture, and beneficial microbial associations. This has narrowed genetic diversity, impacting traits essential for stress resilience and efficient nutrient and water acquisition—factors expected to become increasingly critical under climate change. In this study, we evaluated 36 primary synthetic (PS) hexaploid wheat lines developed by crossing Aegilops tauschii with the durum wheat cultivar Langdon (LNG) and compared them with LNG and the hexaploid variety Norin 61 (N61). We observed significant variation in root length, biomass, and associations with fungal endophytes, including beneficial Arbuscular Mycorrhizal Fungi (AMF) and Serendipita indica, and pathogenic Alternaria sp. Clustering analysis based on these traits identified three distinct PS groups: (1) lines with greater root length and biomass, high AMF and S. indica colonization, and low Alternaria infection; (2) lines with intermediate traits; and (3) lines with reduced root traits and high Alternaria susceptibility. Notably, these phenotypic patterns corresponded closely with the soil classification of the Ae. tauschii progenitors’ origin, such as Cambisols (supportive of root growth), and Gleysols and Calcisols (restrictive of root growth). This highlights the soil microenvironment as a key determinant of belowground trait expression. By comparing PS lines with domesticated tetraploid and hexaploid wheat, we identified and selected PS lines derived from diverse Ae. tauschii with enhanced root traits. Our study emphasizes the potential of wild D-genome diversity to restore critical root traits for breeding resilient wheat.